Converting dependent for loops to parfor
1 view (last 30 days)
Show older comments
Roughly, the code looks like this:
for t=1:NumberOfSteps
F=zeros(1,N)
for i=1:N-1
for j=i+1:N
rij=r(:,i)-r(:,j)
Fij=... %some function of rij
F(:,i)=F(:,i)+Fij
F(:,j)=F(:,j)-Fij
end
end
end
Any idea how to convert this to parfor?
Many thanks!!
0 Comments
Answers (2)
See Also
Categories
Find more on Loops and Conditional Statements in Help Center and File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!